2020
DOI: 10.1096/fj.201902796r
|View full text |Cite
|
Sign up to set email alerts
|

The lack of neuropeptide Y‐Y 1 receptor signaling modulates the chemical and mechanical properties of bone matrix

Abstract: Genetic and pharmacological functional studies have provided evidence that the lack of Neuropeptide Y‐Y1 receptor (Y1R) signaling pathway induces a high bone mass phenotype in mice. However, clinical observations have shown that drug or genetic mediated improvement of bone mass might be associated to alterations to bone extracellular matrix (ECM) properties, leading to bone fragility. Hence, in this study we propose to characterize the physical, chemical and biomechanical properties of mature bone ECM of germl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…It has been observed that BMSC migration and VEGF expression were upregulated after NPY treatment ( 45 ) and increased levels of VEGF stimulate angiogenesis and osteoblastic differentiation of BMSCs ( 59 ). Besides, Y1R signaling disruption is responsible for enhancing the deposition and maturity of collagen and mineral hydroxyapatite layers in the skeletal muscle, and bone mechanical property was furthered improved ( 60 ) ( Figure 1 ).…”
Section: Othersmentioning
confidence: 99%
“…It has been observed that BMSC migration and VEGF expression were upregulated after NPY treatment ( 45 ) and increased levels of VEGF stimulate angiogenesis and osteoblastic differentiation of BMSCs ( 59 ). Besides, Y1R signaling disruption is responsible for enhancing the deposition and maturity of collagen and mineral hydroxyapatite layers in the skeletal muscle, and bone mechanical property was furthered improved ( 60 ) ( Figure 1 ).…”
Section: Othersmentioning
confidence: 99%
“…Conversely, bone mass increased significantly in NPY knockout mice ( Baldock et al, 2009 ). Moreover, bone mass increased significantly in NPY Y1R knockout mice and wild-type (WT) mice treated with Y1R inhibitor because Y1R is expressed in the osteoblasts ( Brothers and Wahlestedt, 2010 ; Sousa et al, 2020 ). Importantly, embryonic stem cells accelerated adipogenesis induced by NPY system activation, which is consistent with our previous observation ( Han et al, 2012 ; Hu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with prior observations, our immunochemistry results showed that Y1R was widely present at the healing site of RC. Moreover, loss of Y1R has been found to induce a high bone mass phenotype with increased deposition of mineral and extracellular matrix [ 33 ]. Sousa DM et al.…”
Section: Discussionmentioning
confidence: 99%